LEARNING AND SCHOOL DEVELOPMENT IN THE HISTORICAL EDUCATIONAL PROCESS - Dias da Silva, Damiana; Martins da Silva , Elizabete; Gomes Leite , Jocileide; das Graças da Silva Souza , Maria; Pereira de Caldas, Marinez (Revista Gênero e Interdisciplinaridade, 2024)
The purpose of this article is to present studies on development and learning about the thoughts of philosophical scholars such as Jean Piaget, Lev Vygotsky and Henrique Wallon, and the theories of Jean Piaget and Henry Wallon are the most complete and articulated theories of psychological development. Piaget denies that his theory is a theory of learning, classifying it as a theory of development. Unlike these two scholars Vygotsky criticizes the theories that separate learning from development. It seeks to understand the origin and development of psychological processes throughout individual history. It places human development, learning and the relationships between development and learning as central themes in their work. The text also brings information about Paulo Freire’s theories about the teaching-learning process. It also reflects on the role of the teacher in teaching learning; The history of education in Brazil; The social role of the school as well as the Brazilian pedagogical trends: traditional, renewed, technicist, liberating and critico-social of the contents. For this we orient ourselves through the scholars mentioned above among other relevant names that study and debate the subject under study.